2019
DOI: 10.1192/bjp.2019.183
|View full text |Cite
|
Sign up to set email alerts
|

Could mindfulness-based cognitive therapy prevent a lifelong recurrent course of depression or anxiety by addressing key mechanisms of vulnerability in high-risk adolescents?

Abstract: SummaryWe explore the potential of mindfulness-based cognitive therapy, a skills-based intervention that provides participants with sustainable tools for adaptive responses to stress and negative mood, for the large group of young people with depression or anxiety who only partially or briefly respond to currently available first-line interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Instead of focusing specifically on changing the form, frequency, or situational sensitivity of bad emotions or thoughts, it advocates individuals improving the capacity of metacognitive awareness of psychological processes, which means taking an accepting attitude to objectively evaluating their emotions or thoughts[ 13 ]. The third-wave CBT methods, such as mindfulness-based cognitive therapy[ 14 ], dialectical behavior therapy[ 15 ], and acceptance and commitment therapy (ACT)[ 16 ], can help depressed adolescents improve their metacognitive awareness, which in turn improve their depressive symptoms. Those approaches represent a paradigm shift in intervention science, called process-based therapy (PBT)[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of focusing specifically on changing the form, frequency, or situational sensitivity of bad emotions or thoughts, it advocates individuals improving the capacity of metacognitive awareness of psychological processes, which means taking an accepting attitude to objectively evaluating their emotions or thoughts[ 13 ]. The third-wave CBT methods, such as mindfulness-based cognitive therapy[ 14 ], dialectical behavior therapy[ 15 ], and acceptance and commitment therapy (ACT)[ 16 ], can help depressed adolescents improve their metacognitive awareness, which in turn improve their depressive symptoms. Those approaches represent a paradigm shift in intervention science, called process-based therapy (PBT)[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that avoidant behavior could directly influence disturbed physical function, filling the gap of existing knowledge. Thus, we can reduce negative emotions and avoidant behavior of frontline medical staff to promote their physical function by adopting interventions like cognitive-behavioral therapy (CBT) ( 55 , 56 ). This knowledge helps to reveal an influential pattern between negative emotion and risk perception, emotion regulation strategy, avoidant behavior tendency, and physical function.…”
Section: Discussionmentioning
confidence: 99%